2020
DOI: 10.1111/pbi.13327
|View full text |Cite
|
Sign up to set email alerts
|

High‐resolution expression profiling of selected gene sets during plant immune activation

Abstract: The plant immune system involves detection of pathogens via both cell-surface and intracellular receptors. Both receptor classes can induce transcriptional reprogramming that elevates disease resistance. To assess differential gene expression during plant immunity, we developed and deployed quantitative sequence capture (CAP-I). We designed and synthesized biotinylated single-strand RNA bait libraries targeted to a subset of defense genes, and generated sequence capture data from 99 RNA-seq libraries. We built… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
3
17
0
Order By: Relevance
“…Infiltration of Pf0-1:AvrRps4 mut activates SRMI, and Pf0-1:AvrRps4 WT activates ‘SRMI+IRMI’ (Supplementary Fig. 5a), as in previous reports 4,8 . We took samples at 4 hours post-infiltration (hpi) for ATAC-seq to monitor early changes during immune activation (Supplementary Fig.…”
Section: Mainsupporting
confidence: 81%
See 3 more Smart Citations
“…Infiltration of Pf0-1:AvrRps4 mut activates SRMI, and Pf0-1:AvrRps4 WT activates ‘SRMI+IRMI’ (Supplementary Fig. 5a), as in previous reports 4,8 . We took samples at 4 hours post-infiltration (hpi) for ATAC-seq to monitor early changes during immune activation (Supplementary Fig.…”
Section: Mainsupporting
confidence: 81%
“…We study the Arabidopsis RPS4/RRS1 NLR pair that detects bacterial effectors AvrRps4 and PopP2. Using a Pseudomonas strain that solely delivers one of these effectors, we defined early RPS4/RRS1-dependent transcriptional responses in Arabidopsis leaves 6,7 , and showed that 4 hours after infiltration, SRMI together with IRMI (‘SRMI+IRMI’) elevates the expression of defense-related genes more strongly compared to SRMI alone 6,8 . This early timepoint precedes accumulation of defense hormone salicylic acid (SA) and gene reprogramming in response to increased endogenous SA level 6,8 .…”
Section: Mainmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of targeted RNA-seq (CaptureSeq) can help resolve this issue by focusing sequencing on genes of interest and allowing the interrogation of low-expressed genes and transcripts that would be missed by conventional methods [2][3][4][5]. Targeted RNA-seq is a widely applicable method and has been successfully utilized to enrich genes and transcripts from mammals [2,3], plants [6], fungi [7], bacteria [8] and viruses [9]. CaptureSeq performs well on different sample types, including formalin-fixed paraffin-embedded (FFPE) samples with highly degraded RNA and has been widely applied to identify molecular alterations in cancer in both research and clinical settings [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%